2009
DOI: 10.1111/j.1742-6723.2009.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of invasive mechanical ventilation in Australian emergency departments

Abstract: The application of mechanical ventilation was similar to descriptions reported in the critical care literature both in Australia and internationally. Decision-making responsibilities were shared by ED medical and nursing staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Even when inadequate mechanical ventilation practices are used for only brief periods, hospital stays are often prolonged, and patients can experience mechanical ventilation-induced injuries 8 - 10 . These consequences are becoming increasingly common across various hospital departments 11 , 12 . Exacerbating the situation, many physicians with no formal training in mechanical ventilation end up managing critically ill patients undergoing this intervention 13 - 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Even when inadequate mechanical ventilation practices are used for only brief periods, hospital stays are often prolonged, and patients can experience mechanical ventilation-induced injuries 8 - 10 . These consequences are becoming increasingly common across various hospital departments 11 , 12 . Exacerbating the situation, many physicians with no formal training in mechanical ventilation end up managing critically ill patients undergoing this intervention 13 - 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In the final analysis, 21 studies were included. Eleven studies provided outcome data and were meta-analyzed (6, 11, 28, 35–42); 10 studies provided descriptive tidal volume data (16–18, 43–49). Supplemental Digital Content 5 (http://links.lww.com/CCM/H45) displays the study flow diagram at each stage of the review.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found that ICU crowding, with ICUs functioning at greater than 20% above the average annual census, was associated with an increased ED LOS. 29 With these dual factors of increasing acuity with worsening crowding, the incidence of mechanically ventilated patients in the ED is growing 37 and their LOS in the ED is increasing. 22 EPs, therefore, may be primarily responsible for prolonged management of mechanically ventilated patients.…”
Section: Discussionmentioning
confidence: 99%